Exploring patient’s clinical outcomes, hospital costs, and satisfaction after the implementation of integrated clinical pathway-based nursing practice model - Rini Rachmawaty; Elly Wahyudin; Agussalim Bukhari (Cost Effectiveness and Resource Allocation)
Abstract Introduction Hospitals provide essential health services, focusing on quality, safety, and patient-centered care. The rising prevalence of communicable and non-communicable diseases in Indonesia has led to increased National Health Insurance (NHI) costs, with communicable diseases representing a significant burden despite global progress in disease control. Tuberculosis remains a major global health concern, causing 1.25 million deaths in 2023, while Indonesia ranks second globally for tuberculosis burden, accounting for 10% of global TB cases with an estimated 969,000 cases annually. Despite efforts to improve quality, Haji and Labuang Baji Hospitals face challenges, including financial losses and suboptimal patient outcomes. This study aims to assess the impact of an Integrated Clinical Pathway (ICP)-based Professional Nursing Practice Model on clinical outcomes, hospital costs, and patient satisfaction at these hospitals. Methods This study employed action research methodology by developing, implementing, and evaluating the clinical guidelines and ICP for 10 diseases that were categorized as high volume, high risk, and high cost based on secondary data analysis using the NHI databases. Data was collected through observation of the ICP implementation on 40 patients and interviews of Professional Care Providers (PCPs) and was analyzed using IBM SPSS Statistics version 28. Results A total of 40 patients from Haji Hospital (n = 20) and from Labuang Baji Hospital (n = 20) with diagnoses of pulmonary tuberculosis, pneumonia, dyspepsia, typhoid fever, normal delivery, and COPD were included and analyzed. Compliance with ICPs in both hospitals was quite low: 50.02% in Haji Hospital and 44.46% in Labuang Baji Hospital. However, the length of patients’ stays (LOS) generally complied with ICP standards, although some cases exceeded the benchmarks. Hospital costs varied across different disease diagnoses, impacting overall financial outcomes. Patient satisfaction improved across all diagnostic categories. Conclusion The implementation of ICP at both hospitals showed that all indicators of patient clinical outcomes improved according to the time specified in ICP, resulting in patients’ LOS being shorter than stipulated in ICP and an increase in patient satisfaction. ICP implementation has also led to hospitals earning different profits in almost all diagnoses.